Maastrichtian ammonites from the Hornerstown Formation in New Jersey - Kennedy, W; Cobban, W (1996)
The base of the Paleocene Hornerstown Formation at the Inversand pit and certain other localities in New Jersey yields a diverse phosphatised fauna of Maastrichtian age, including the ammonites Pachydsicus (Neodesmoceras) mokotibensis Collignon, 1952, Sphenodiscus lobatus (Tuomey, 1854), Baculites spp., and Eubaculites carinatus (Morton, 1834). S. lobatus is known from the older Red Bank Sand and Tinton Sand in New Jersey; the other species are known only from the basal Hornerstown. Occurrences at the Inversand pit are regarded as either reworked or remainie, although details of Cretaceous/Paleocene boundary events have been destroyed by pervasive burrowing that pipes the Hornerstown down into the underlying Navesink Formation.